2018
DOI: 10.1002/2017jc012943
|View full text |Cite
|
Sign up to set email alerts
|

Directional Wave Spectra Observed During Intense Tropical Cyclones

Abstract: Two deep‐sea moorings were deployed 780 km off the coast of southern Taiwan for 4–5 months during the 2010 typhoon season. Directional wave spectra, wind speed and direction, and momentum fluxes were recorded on two Extreme Air‐Sea Interaction buoys during the close passage of Severe Tropical Storm Dianmu and three tropical cyclones (TCs): Typhoon Fanapi, Super Typhoon Megi, and Typhoon Chaba. Conditions sampled include significant wave heights up to 11 m and wind speeds up to 26 m s−1. Details varied for larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
46
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 54 publications
3
46
1
Order By: Relevance
“…For instance, this is the case in the cyclone's left forward quadrant where the direction of wind deviates considerably from the wave direction [31]. As shown in a previous study [11], the analysis of directional spectra observed by Extreme Air-Sea Interaction buoys shows that a variety of spectral geometries can exist close to the eyes of typhoons. Thus, the effectiveness of the simple fetch-limited parametric models should be further discussed, in terms of the cyclone quadrant under consideration, and the rate of development or change the intensity of the storm.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…For instance, this is the case in the cyclone's left forward quadrant where the direction of wind deviates considerably from the wave direction [31]. As shown in a previous study [11], the analysis of directional spectra observed by Extreme Air-Sea Interaction buoys shows that a variety of spectral geometries can exist close to the eyes of typhoons. Thus, the effectiveness of the simple fetch-limited parametric models should be further discussed, in terms of the cyclone quadrant under consideration, and the rate of development or change the intensity of the storm.…”
Section: Discussionmentioning
confidence: 54%
“…Moreover, many studies have shown that most of the spectra are monomodal under extreme conditions, similar to the spectra generated under fetch-limited, steady wind conditions. However, bi-modal spectra are also found in both measurements and model results under intense cyclone conditions [11,29,31], in which case the accuracy of the parametric models used in this study can be degraded. For instance, this is the case in the cyclone's left forward quadrant where the direction of wind deviates considerably from the wave direction [31].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…New techniques and algorithms are continuously proposed to improve the retrieval of TC properties from Earth orbiting satellites; for example, Shao et al () improved estimation of TC wind speeds by exploiting wind‐generated waves extracted from spaceborne synthetic aperture radar (SAR). Intensive and well‐organized projects are usually an auspice of significant progress in the ocean‐TC studies, such as the Coupled Boundary Layer Air‐Sea Transfer (CBLAST) experiment (Black et al, ) and the Impact of Typhoons on the Ocean in the Pacific (ITOP) project (Collins et al, ; D'Asaro et al, ; Potter et al, ). Recently, in order to collect a chronic and three‐dimensional perspective on changes to the water column during TCs, a series of mooring/buoy arrays are deployed in the northern South China Sea (Zhang et al, ) where historical statistics show that typhoon has the highest occurrence probability.…”
mentioning
confidence: 99%